The World Bank & International Finance Corporation - World Bank. (Washington, D.C., U.S.A. : The Bank, 1983)
The IBRD, IDA, and the IFC have three interrelated functions: to lend funds, to provide advice, and to serve as a catalyst to stimulate investment by others
osc 7/09/2021
Loans
Keywords: World Bank